Amylose Inter-Chain Entanglement and Inter-Chain Overlap Impact Rice Quality - Changfeng Li; Yi Ji; Shaobo Zhang; Xiaoyan Yang; Robert G. Gilbert; Songnan Li; Enpeng Li (Foods, 2022)
Retrogradation of cooked rice happens in two ways: one is by the formation of ordered structures, and the other is through intra- and inter-chain entanglement and inter-chain overlap, which in turn are affected by the amylose chain-length distribution. Both entanglement and overlap could affect rice texture. Here, four amylose samples were isolated from starch by precipitation from a dimethyl sulfoxide solution with butan-1-ol and isoamyl alcohol. Following enzymatic debranching, they were then characterized using size-exclusion chromatography. Amylose solutions (10%, m/v) were made by dissolving amylose in 90% (v/v) DMSO. Amylose gels (10%, w/v) were made by dissolving amylose powders into hot water, followed by cooling. The rigidity of the amylose gels and the structural order were measured using a texture analyzer and X-ray diffractometer, respectively. In the amylose solution, for a given mass of polymer in a fixed amount of solvent, the total occupied volume was reduced when the polymer molecular weight was smaller, resulting in less inter-chain overlap and a lower viscosity of the amylose solution. The overall mobility and diffusion of the molecules were inversely related to the square of the molecular weight until the gelation concentration. Thus, amylose gels in which amylose had a lower molecular weight had a greater chance to permeate into other molecules, which counterintuitively led to more inter-chain entanglement and more rigid amylose gels during retrogradation. This information could help rice breeders improve rice quality by using the molecular structure of starch as a guide.